Utilization of Different Carbon Sources by Nordic Microalgae Grown Under Mixotrophic Conditions - Plöhn, Martin; Scherer, Kim; Stagge, Stefan; Jönsson, Leif J.; Funk, Christiane (Frontiers in Marine Science, 2022)
Microalgae are promising candidates for sustainable wastewater treatment coupled to the production of biofuel, bioplastic and/or bio-fertilizers. In Nordic countries, however, light is a limiting factor for photosynthesis and biomass production during the winter season. Compared to municipal wastewater, industrial wastewater streams from the pulp and paper industry contain lower amounts of nitrogen, but high concentrations of carbon sources, which could be utilized by microalgae to enhance biomass production in limiting light. This study focused on the utilization of methanol, glycerol and xylose by five different Nordic microalgae [Chlorella vulgaris (13–1), Coelastrella sp. (3–4), Desmodesmus sp. (2–6), Chlorococcum sp. (MC1) and Scotiellopsis reticulata (UFA-2)] grown under mixotrophic conditions. Two of these strains, i.e., Chlorococcum sp. (MC1) and Scotiellopsis reticulata (UFA-2) were able to grow in the presence of xylose or methanol at concentrations of 6 g L–1, or 3%, respectively, in a 12/12 h day/night cycle. HPLC analysis confirmed the consumption of those substrates. Glycerol (2.3 g L–1) was tolerated by all strains and increased growth for Chlorella vulgaris (13–1), while higher concentrations (20 g L–1) were only tolerated by Chlorococcum sp. (MC-1). Fourier-transform infrared spectroscopy, performed after growth in presence of the dedicated carbon source, indicated an increase in the fingerprint region of the carbohydrate fraction. This was particularly the case for Chlorococcum sp. (MC1), when grown in presence of glycerol, and Scotiellopsis reticulata (UFA-2), when grown in presence of xylose. Therefore, these strains could be potential candidates for the production of biofuels, e.g., bioethanol or biogas. We could show that Nordic microalgae are able to grow on various carbon sources; the actual uptake rates are low during a 12/12 h day/night cycle requesting additional optimization of the cultivation conditions. Nonetheless, their potential to use pulp and paper waste-streams for cheap and sustainable biomass production is high and will support the development of new technologies, turning waste-streams into resources in a circular economy concept.